2022
DOI: 10.1186/s12882-022-02910-8
|View full text |Cite
|
Sign up to set email alerts
|

Using CUSUM in real time to signal clinically relevant decreases in estimated glomerular filtration rate

Abstract: Background The electronic health record (EHR), utilized to apply statistical methodology, assists provider decision-making, including during the care of chronic kidney disease (CKD) patients. When estimated glomerular filtration (eGFR) decreases, the rate of that change adds meaning to a patient’s single eGFR and may represent severity of renal injury. Since the cumulative sum chart technique (CUSUM), often used in quality control and surveillance, continuously checks for change in a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The goal of CUSUM GFR -based screening is to detect a clinically meaningful decline in eGFR as an early indicator for the risk of progression to severe stages of CKD and ESKD. A previous study showed the validity of using a statistical measure, CUSUM GFR , based on patients’ longitudinal eGFR values—a measure that only requires a highly accessible blood test, the basic metabolic panel (BMP)—for early detection of severe CKD [ 19 ]. For an individual patient, the CUSUM GFR statistic was updated after each measurement and captured the historical information accumulated from all prior eGFR observations.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of CUSUM GFR -based screening is to detect a clinically meaningful decline in eGFR as an early indicator for the risk of progression to severe stages of CKD and ESKD. A previous study showed the validity of using a statistical measure, CUSUM GFR , based on patients’ longitudinal eGFR values—a measure that only requires a highly accessible blood test, the basic metabolic panel (BMP)—for early detection of severe CKD [ 19 ]. For an individual patient, the CUSUM GFR statistic was updated after each measurement and captured the historical information accumulated from all prior eGFR observations.…”
Section: Methodsmentioning
confidence: 99%
“…For an individual patient, the CUSUM GFR statistic was updated after each measurement and captured the historical information accumulated from all prior eGFR observations. Specifically, CUSUM GFR is defined as follows [ 19 ]: where eGFR i indicates the eGFR measured at the i th observation, indicates the standard deviation of eGFR in a matched group of patients without chronic or acute kidney disease (CKD or AKD) diagnosis that was determined using ICD9/10 codes [ 19 ], and is the age-adjusted mean eGFR which decreases by 0.81 mL/min/1.73 m 2 annually. The variable w is the tuning parameter for the CUSUM GFR statistic.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations